Complementation Test of Rpe65 Knockout and Tvrm148 - Wright, Charles B. (The Association for Research in Vision and Ophthalmology, 2013)
PURPOSE. A mouse mutation, tvrm148, was previously reported as resulting in retinal degeneration. Tvrm148 and Rpe65 map between markers D3Mit147 and D3Mit19 on a genetic map, but the physical map places RPE65 outside the markers. We asked if Rpe65 or perhaps another nearby gene is mutated and if the mutant reduced 11-cis-retinal levels. We studied the impact of the tvrm148 mutation on visual function, morphology, and retinoid levels. METHODS. Normal phase HPLC was used to measure retinoid levels. Rpe65(+/+), tvrm148/+ (T(+/−)), tvrm148/tvrm148 (T(−/−)), RPE65(KO/KO) (Rpe65(−/−)), and Rpe65(T/−) mice visual function was measured by optokinetic tracking (OKT) and electroretinography (ERG). Morphology was assessed by light microscopy and transmission electron microscopy (TEM). qRT-PCR was used to measure Rpe65 mRNA levels. Immunoblotting measured the size and amount of RPE65 protein. RESULTS. The knockout and tvrm148 alleles did not complement. No 11-cis-retinal was detected in T(−/−) or Rpe65(−/−) mice. Visual acuity in Rpe65(+/+) and T(+/−) mouse was ∼0.382 c/d, but 0.037 c/d in T(−/−) mice at postnatal day 210 (P210). ERG response in T(−/−) mice was undetectable except at bright flash intensities. Outer nuclear layer (ONL) thickness in T(−/−) mice was ∼70% of Rpe65(+/+) by P210. Rpe65 mRNA levels in T(−/−) mice were unchanged, yet 14.5% of Rpe65(+/+) protein levels was detected. Protein size was unchanged. CONCLUSIONS. A complementation test revealed the RPE65 knockout and tvrm148 alleles do not complement, proving that the tvrm148 mutation is in Rpe65. Behavioral, physiological, molecular, biochemical, and histological approaches indicate that tvrm148 is a null allele of Rpe65.